2020
DOI: 10.1186/s12995-020-00269-w
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-induced injuries in workers exposed to transient and high frequency vibrations

Abstract: Background: The risk of developing vibration white fingers and neurosensory symptoms increases with the duration and intensity of the exposure. The aim of this study was to investigate the risk of developing vibration white fingers (VWF), neurosensory symptoms and musculoskeletal disorders among workers exposed to transient and high frequency vibrations. Methods: The study included 38 vibration exposed workers from a loader assembly plant in Sweden (30 males and 8 females). All participants answered questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
1
27
1
2
Order By: Relevance
“…Furthermore, despite the fact that the quarry workers worked outdoors and were exposed to cold as well as to hand-arm vibrations during the winter period, their prevalence of VWF was very low compared to their prevalence of neurosensory findings (40%). The same tendency has been published recently, in a study from a loader assembly plant in Sweden (Gerhardsson et al 2020 ) where the workers had a high exposure to high-frequency vibrations. Thus, several studies indicate that high-frequency vibrations increase the risk for developing neurosensory symptoms and that the nervous system may be more susceptible to exposure to high-frequency vibrations than the vascular system.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, despite the fact that the quarry workers worked outdoors and were exposed to cold as well as to hand-arm vibrations during the winter period, their prevalence of VWF was very low compared to their prevalence of neurosensory findings (40%). The same tendency has been published recently, in a study from a loader assembly plant in Sweden (Gerhardsson et al 2020 ) where the workers had a high exposure to high-frequency vibrations. Thus, several studies indicate that high-frequency vibrations increase the risk for developing neurosensory symptoms and that the nervous system may be more susceptible to exposure to high-frequency vibrations than the vascular system.…”
Section: Discussionsupporting
confidence: 81%
“…In an on-going Swedish study from a load assembly plant (Gerhardsson et al 2020 ), 38 vibration exposed workers (30 males, 8 females) were studied. The prevalence of VWF was 30% among the male workers and 50% among the females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure inside the cubital tunnel has also been shown to increase during the contraction of the exor carpi ulnaris muscle 26 . Vibration causes vasoconstriction, smooth muscle wall hypertrophy, periarterial brosis, and damage to the endothelial cells 27 . A histological model showed that tissue oedema and vasospasm from vibration leads demyelination and perineural brosis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A study that depicts the relationship between vibration amplitude and musculoskeletal disorder (MSD) symptoms in dental hygiene students showed that MSD symptoms might increase abruptly using manual and ultrasonic hand pieces [ 8 ]. The effect of grip force, hand posture, and the accelerometer’s location on hand piece on vibration amplitude were also studied [ 9 ]. Through vibration exposure from a specially designed handle, researchers looked at gender differences in the amount of vibration absorption per unit of time.…”
Section: Introductionmentioning
confidence: 99%